1 PENGARUH LAMA PENCELUPAN TERHADAP WARNA YANG DIHASILKAN PADA BAHAN SUTERA MENGGUNAKAN ZAT WARNA ALAM EKSTRAK DAUN PURING (Codiaeum Variegatum) DENGAN MORDAN JERUK NIPIS (Citrus Aurantifolia) - Saputri, Rien Ana; Adriani, Adriani; Nelmira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of this study to describe the dark-light color (value), the flatness of the color, the intensity of the color (chroma) and describe the dark-light color (value), the flatness of color, and color intensity (chroma) to the effects of differences in long immersion. Data obtained in the form of primary data sourced from 15 panelists, then the collected data is processed and analyzed analysis of varianceone. Results dyeing time of 15 minutes to produce a color Pale Violet Red #D26990. Immersion with 30 minutes to produce a color Mulberry Violet #C55F88. Immersion with 45 minutes to produce a color Mulberry Violet #D75880. For light and dark colors (value) is Fcount ≤ Ftable = 2.344 ≤ 3.22 Then Ho is accepted, meaning that there is no significant effect due to differences in long dyeing. Flatness color is Fcount > Ftable = 12 011 > 3.22 So Ha accepted, meaning that there is significant influence due to differences in long dyeing.The intensity of the color (chroma) is Fcount ≤ Ftable = 2.662 ≤ 3.22 Then Ho is accepted, meaning that there is no significant effect due to differences in long dying.Keywords: Effect time dyeing, croton leaf extract